KREASI DAUN PISANG PADA BAJU KURUNG BASIBA - Tastail Amelia; Dini Yanuarmi; Taufik Akbar; Mega Kencana (Institut Seni Indonesia Padangpanjang, 2022)
The banana plant is a fruit plant consisting of roots, stems, leaves, a banana heart and fruit. Banana leaves are often used to wrap food. Banana leaves consist of a petiole, leaf blade and midrib in the middle of the leaf. Banana leaves were created as a motif in the creation of the kuruang basiba shirt. The concept of creating a banana leaf shape creation through a study of the shape of a banana leaf which is realized in the design of textile craft works as a kuruang basiba shirt. The creation method begins with the exploration stage, the planning stage, and the embodiment stage. The creation of artwork uses the theoretical basis of form, function, aesthetics, creation, motif, and colour. This work is done with Mayang embroidery techniques and ribbon and thread embroidery, which is used to unite all pieces of cloth into a kuruang basiba shirt with the motif applied to the work, namely the creation of a banana leaf shape. The result of the product of embroidery work with the motif of the banana leaf shape is manifested on the kuruang basiba shirt.